9. UPAYA PEMBERDAYAAN MASYARAKAT YANG DIDASARI PARTISIPASI WANITA SEBAGAI PETUGAS PELAYANAN KESEHATAN DI KECAMATAN MLONGGO KABUPATEN JEPARA - Widagdo, Laksmono (FORUM, 2007)
The integrated health and family planning services (Posyandu) forms one of the community based health efforts done by women and is strategy to ensure child survival as well as their mental and physical development and protection. Secondary research indicates that women participation can not rise by itself and that it must by continuously motivated by other parties. These include the government and non-government organizations, as well as from within the communities. Motivations from government and non-government organizations are often temporary, while motivations from the community are often expected to be sustainable. In its implementation, however, the Posyandu often face many impediments and failures, though some have been successful. One of the main failures is reflected in the drop-out rates of the women village kader due to the lack of motivation especially from the village heads (kades). The qualitative research was done in stages focusing on characteristics of leadership, while a quantitative analysis through a cross sectional survey was done to show the significance of such leadership. The results both qualitative and quantitative analysis show a relation between leadership and women village kaders attitude and a relation between leadership and the achievement of posyandu programs significantly. It means that drop-out rates of women village kaders are indeed affected by kades leadership which also affects the overall performance of the posyandu.